An Interpretive Framework for Cost. - Haseman, Wilber C. (The Accounting Review, 1968)
Abstract The purpose of this article is to examine the meaning or meanings of the term, cost, in a comprehensive way, with the objective of providing an interpretive framework to assist in communicating cost information with greater precision and, thus, to assist in utilizing cost information more effectively. Such an interpretive framework should be useful to accountants charged with the responsibility of compiling and communicating cost information, and to the users of cost information whose conclusions and/or decisions depend at least partly upon an interpretation of this information. Accounting measurements of cost are used in manifold ways to express different aspects of enterprise operations. These uses for cost measurements frequently require different interpretations of cost, and it is in this regard that confusion may arise. For the purpose of planning and as a basis for identifying waste and inefficiency, anticipated costs are needed. In most regards concepts underlying anticipated costs are the same as those previously discussed in relation to historical and current costs.